100 YEARS OF THE FIRST SURGICAL DEPARTMENT OF KEMEROVO - Подолужный, Валерий Иванович; Павленко, Владимир Вячеславович; Каменева, Евгения Александровна; Старцев, Андрей Борисович; Радионов, Игорь Александрович; Кокоулина, Юлия Андреевна (Medicine in Kuzbass, 2024)
Let us recall the years of work of the first surgical department of the city of Kemerovo, which is associated with the stages of development of the surgical service of the city and the region as a whole. All these years the department has been ready to provide emergency surgical care to the population of the city and the region around the clock, keeps pace with the development of surgical technologies, introduces new things and is an important clinical base for training surgical personnel for Kuzbass.